Molecular epidemiology of adenoviruses: global distribution of adenovirus 7 genome types - Wadell, Goran (1985)
Adenovirus 7 (Ad7) is the adenovirus species that most frequently has been associated with severe illness. Seven distinct genome types of adenovirus 7, Ad7p, Ad7a, Ad7b, Ad7c, Ad7d, Ad7e, and Ad7f, can be identified by using restriction endonucleases BamHI and SmaI. We analyzed the distribution of the different Ad7 genome types among 314 isolates frolli patients and healthy shedders. The Ad7b and Ad7c genome types accounted for 90% of the isolates from patients and appeared to be mutualIy exclusive. A shift ftom Ad7c to Ad7b genome types occurred in 1969 in Europe and in 1975 in Australia. During the last decade, Ad7b genome types predominated in Australia, Europe, and North America. Ad7c was detected in South Africa, Ad7d was detected in China, Ad7e was detected in Brazil, and Ad7f was detected in Australia. The Ad7p and Ad7a genome types dominated among isolates obtained from healthy shedders and appeared scattered through the years and the geographical areas. The prevalence of Ad7 infections is high in Japan as judged by the herd immunity. However, the low percentage (2 %) of Ad7 isolates amongaQ adenovirus isolates chiefly from patients, coupled with 30 to 50% antibody prevalence, argues for a high proportion of inapparent infections and, hence, Ad7 strain(s) of low pathogenicity.